THE GRAMMATICAL CATEGORIES OF VERBS IN ENGLISH AND UZBEK IN GENERAL - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article explores the structural inconsistencies in English and Uzbek, providing specific examples of differences and similarities between the two languages. In this post, we will learn how to use the Grammar Verb Categories in both languages [1]. Key words: English, Uzbek, verb, suffixes, order, numerals, nouns, grammatical transformations, syntactic constructions, pronouns, articles, gender, tenses and other grammatical categories.